Report on the Observance of Standards and Codes on Accounting and Auditing Update : Czech Republic - World Bank (World Bank, Vienna, 2016)
Reports on the Observance of Standards and Codes (ROSC) Accounting and Auditing (A&A) assess accounting and auditing practices in participating countries. They form part of a joint initiative that is implemented by the World Bank and the International Monetary Fund to review the quality of implementation of twelve internationally recognized core standards (the ROSC program). These standards and their related codes are relevant to economic stability and private and financial sector development. The program was developed at the end of the 1990s, in the wake of financial crises that affected many countries in several regions of the world. Since its inception in early 2000, the ROSC A&A program has concluded evaluations of the A&A environment in more than one hundred countries around the world. ROSC A&A reports have been produced for all countries of the Europe and Central Asia Region, except Russia. Initiatives to reassure investors about the quality of financial reporting of public interest entities, including listed companies, banks and insurance companies will also be essential.